Improving Drama Script Writing through Modeling Strategies - Widodo, Suyud; Lustyantie, Ninuk (IJLECR (International Journal of Language Education and Cultural Review), 2016)
This action research refers to Elliot model (1991) that aims to improve the ability of writing a screenplay through modeling strategies. This action researchon SMA of Purbolinggo Lampung in the academic year of 2014/2015. The implementation of this research is three cycles. Each implementation of actions is divided into stages, identifying intial idea, reconnaissance, general planning, implement of action, monitor implemention, reflection, reconnaissance and revise general idea. The results of the reflection activities function as a foothold to draw up a plan of action to the next cycle. The research results can be concluded: the first process of improving writing skills through drama script modeling strategy. Second, the results of the upgrade script writing drama through modeling strategies, ranging from initial tests as exploitation of the capabilities of the beginning to the end of the test third cycle the experience increased. (1) The results of initial tests average score 40.1 ((level less); (2) the first cycle the average score 42.4 (level less); (3) the second cycle the average score 64.3 (level of being); and (4) the third cycle the average score 83.4. This score has already reached a high level.